2014
DOI: 10.4238/2014.august.28.17
|View full text |Cite
|
Sign up to set email alerts
|

A study of microemboli monitoring of atherosclerotic thrombotic cerebral infarction and artery stenosis

Abstract: ABSTRACT. This study aimed to assess the relationship between the recurrence and prognosis of patients with acute middle cerebral artery infarction, atherosclerotic brain infarction, and the existence of microemboli. We continuously enrolled patients with acute atherosclerotic thrombotic cerebral infarction artery stenosis. We performed transcranial Doppler color ultrasound micro emboli monitoring, color Doppler ultrasound carotid artery tests, intracranial Microemboli monitoring study and carotid artery magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
10
1
1
Order By: Relevance
“…Our finding of no difference between symptomatic and asymptomatic status differ from others (Salem, et al 2011, Siebler, et al 1994, Sun, et al 2014, Tegos, et al 2001) in which microemboli were more prevalent in symptomatic patients. Our findings also differ from others (Sitzer, et al 1995) in that we did not see any macroscopic nor microscopic differences in plaque between the symptomatic and asymptomatic groups.…”
Section: Discussioncontrasting
confidence: 89%
“…Our finding of no difference between symptomatic and asymptomatic status differ from others (Salem, et al 2011, Siebler, et al 1994, Sun, et al 2014, Tegos, et al 2001) in which microemboli were more prevalent in symptomatic patients. Our findings also differ from others (Sitzer, et al 1995) in that we did not see any macroscopic nor microscopic differences in plaque between the symptomatic and asymptomatic groups.…”
Section: Discussioncontrasting
confidence: 89%
“…In the MR imaging, T2-weighted images showed high signal of infarcted tissue in the model group. MR imaging has always been a useful tool in monitoring development of CI [18]. Meanwhile, TTC staining of brain tissues showed visible white infarcted tissue at the left side rat brain arteries in the model group.…”
Section: Discussionmentioning
confidence: 97%
“…Nineteen studies, with a total of 5570 individual patients, reported stroke as an outcome along with data for TCD recording of microembolic signals (7)(8)(9)(10)13,16,(18)(19)(20)23,(27)(28)(29)(30)(31)(32)(33)(34). The sensitivity and specificity were 73.14 (95% CI 48.16 to 88.86) and 70.27 (95% CI 58.61 to 79.78)* respectively.…”
Section: Strokementioning
confidence: 99%